Earth's oldest (approximately 3.5 Ga) fossils and the 'Early Eden hypothesis': questioning the evidence. - Brasier, M; Green, O; Lindsay, J; Steele, A (2004)
We question the biogenicity of putative bacterial and cyanobacterial 'microfossils' from 3465 Ma Apex cherts of the Warrawoona Group in Western Australia. They are challenged on the basis of integrated multidisciplinary evidence obtained from field and fabric mapping plus new high-resolution research into their context, sedimentology, filament morphology, 'septation' and arrangement. They cannot be distinguished from (and are reinterpreted as) secondary artefacts of amorphous carbon that formed during devitrification of successive generations of carbonaceous hydrothermal dyke vein quartz. Similar structures occur within associated carbonaceous volcanic glass. The null hypothesis of an abiotic or prebiotic origin for such ancient carbonaceous matter is sustained until mutually supporting contextural, morphological and geochemical evidence for a bacterial rather than abiotic origin is forthcoming.